Engagement of Families Attending Early Childhood Services During 5-Month School Closure Due to COVID-19: An Italian Experience - Nossa, Roberta; Biffi, Emilia; Colnago, Giovanna; De Gregorio, Giovanna; Saudelli, Laura; Reni, Gianluigi; Caruso, Christian (Frontiers in Psychology, 2021)
During the COVID-19 outbreak, we experienced the suspension of both work-related and spare activities, with the closure of shops, companies, services, as well as schools. Children probably are the ones who have suffered the most from this situation, due to the limited socialization with peers and boredom experienced at home. In this context, schools and childhood services tried to relieve the negative effects brought by the pandemic through actions aimed at actively engaging students and their parents in promoting child development and wellbeing. Therefore, several worldwide actions have been implemented to guarantee educational continuity. However, most of these actions targeted 3–18years old children/adolescents, while the subgroup 0–3 was rarely included. Cooperativa Sociale Aeris, a social enterprise based in northern Italy that deals with socio-educational and welfare services, took several measures to overcome problems resulting from the closure of its services dedicated to 0–3 aged children. In this manuscript, we depict how Aeris kept engaged children and their parents, reporting families’ evaluation on the actions taken. For assessing their proposed activities, Aeris promptly distributed an on-line survey to the families in May 2020. The answers showed that the organized activities had a positive impact on both children and parents, diminishing the sense of loneliness and boredom for the former, and acting as an important support for the latter. Therefore, this manuscript could work as a reference for policy-makers and managers of educational services in implementing activities and initiatives during home schooling.